Burden of copy number variation in common variable immunodeficiency. (July 2014) - Keller, M.; Glessner, J.; Resnick, E.; Perez, E.; Chapel, H.; Lucas, M.; Sullivan, K. E.; Cunningham‐Rundles, C.; Orange, J. S.; Hakonarson, H.
Summary Common variable immunodeficiency (CVID) has been associated recently with a dramatic increase in total copy number variation burden, the cause of which is unclear. In order to explore further the origin and clinical relevance of this finding, we quantified the total genomic copy number variation (CNV) burden in affected patients and evaluated clinical details in relationship to total CNV burden. No correlation was found between total CNV burden and either patient age or time elapsed since symptom onset, and higher total burden did not correlate with incidence of malignancy or other subphenotypes. These findings suggest that the increased CNV burden is static and intrinsic to CVID as a disease.